Machine Perfusions in Liver Transplantation: The Evidence‐Based Position Paper of the Italian Society of Organ and Tissue Transplantation. Issue 10 (17th September 2020) - Ghinolfi, Davide; Lai, Quirino; Dondossola, Daniele; De Carlis, Riccardo; Zanierato, Marinella; Patrono, Damiano; Baroni, Stefano; Bassi, Domenico; Ferla, Fabio; Lauterio, Andrea; Lazzeri, Chiara; Magistri, Paolo; et al.
Abstract : The use of machine perfusion (MP) in liver transplantation (LT) is spreading worldwide. However, its efficacy has not been demonstrated, and its proper clinical use has far to go to be widely implemented. The Società Italiana Trapianti d'Organo (SITO) promoted the development of an evidence‐based position paper. A 3‐step approach has been adopted to develop this position paper. First, SITO appointed a chair and a cochair who then assembled a working group with specific experience of MP in LT. The Guideline Development Group framed the clinical questions into a patient, intervention, control, and outcome (PICO) format, extracted and analyzed the available literature, ranked the quality of the evidence, and prepared and graded the recommendations. Recommendations were then discussed by all the members of the SITO and were voted on via the Delphi method by an institutional review board. Finally, they were evaluated and scored by a panel of external reviewers. All available literature was analyzed, and its quality was ranked. A total of 18 recommendations regarding the use and the efficacy of ex situ hypothermic and normothermic machine perfusion and sequential normothermic regional perfusion and ex situ MP were prepared and graded according to the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) method. A critical and scientific approach is required for the safe implementation of this new technology. Abstract : https://www.wileyhealthlearning.com/Activity/7160712/disclaimerspopup.aspx